Morphologic and quantitative study of the myenteric neurons of the jejunum of malnourished rats (Rattus norvegicus) - MARCÍLIO HUBNER DE MIRANDA NETO; SONIA LUCY MOLINARI; SANDRA REGINA STABILLE; DÉBORA DE MELLO GONÇALES SANT'ANA; MARIA RAQUEL MARÇAL NATALI (Arquivos de Neuro-Psiquiatria)
We studied the effects of maternal proteic desnutrition on the neurons of the myenteric plexus of the jejunum of rats from Rattus norvegicus species. It was used litters of female rats which received diet with normal proteic level during gestation and lactation (group NN), normal diet during gestation and hypoproteic diet during lactation (group ND); hypoproteic diet during gestation and normal diet during lactation (group DN); hypoproteic diet during both gestation and lactation (group DD). After weaning all the animals received diet of normal proteic level until the 60th day of age, when they were killed. The jejunum of the animals was subjected to whole-mount preparations stained by the method of Giemsa and used for the morphologic and quantitative analyses of the neurons of the myenteric plexus. We verified that maternal proteic malnutrition does not cause decrease on the number of myenteric neurons per unit area of jejunum in rats, but elicits mechanisms which assure that, when the animal again receives normal proteic level diet (22%) there occurs storage of proteic material on the cytoplasm of the neurons, thus rendering them larger and strongly basophylic.